Pendidikan Berbasis Moderasi Beragama sebagai Implementasi Rahmatan Lil 'Alamin - Dadan Mardani; Iis Susiawati; Muhammad Faiz Alhaq (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
Education should be designed and implemented by providing space for every human being who wants to know and improve their religious abilities, as well as the potential for soft skills so that human beings are created in accordance with their physical and spiritual nature. The internalization of religious moderation in the educational environment is evidenced by the development of knowledge related to good tolerance and the application of tolerance awareness in the educational environment. This research is a library research, and library data is ready-to-use and is a secondary source which is then analyzed using qualitative descriptive data analysis. the results found are that the educational space can be a means of information and understanding of religious moderation in the midst of diversity for the realization of peace and prosperity in the life of religion and the nation of Indonesia. In conclusion, religious moderation is a religious attitude that is balanced between the practice of one's own religion and respect for the religious practices of other people of different beliefs. Education space has a big role in forming a moderate generation that will become the generator of human civilization.Keywords: Education, Moderation, Religion, Rahmatan lil 'Amen Abstrak:Pendidikan hendaknya dirancang dan dilaksanakan dengan memberikan ruang bagi setiap insan yang ingin mengetahui serta meningkatkan kemampuan beragamanya, begitu pula dengan potensi soft skillnya agar tercipta manusia yang sesuai dengan fitrah lahiriyah dan bathiniyahnya. Internalisasi moderasi beragama di lingkungan pendidikan, dibuktikan dengan dibangunnya pengetahuan terkait toleransi yang baik dan penerapan kesadaran toleransi di lingkungan pendidikan. Penelitian ini merupakan penelitian kepustakaan, dan data pustaka bersifat siap pakai serta merupakan sumber sekunder yang kemudian dianalisis dengan menggunakan analisis data deskriptif kualitatif. hasil yang ditemukan adalah bahwa ruang pendidikan dapat menjadi sarana informasi dan pemahaman akan moderasi beragama yang berada di tengah keragaman demi terwujudnya kedamaian dan kesejahteraan kehidupan keagamaan dan kebangsaan negara Indonesia. Simpulannya moderasi beragama merupakan sikap beragama yang seimbang antara pengamalan agama sendiri dan penghormatan kepada praktik beragama orang lain yang berbeda keyakinan. Ruang pendidikan memiliki peran besar dalam membentuk generasi yang moderat yang akan menjadi pembangkit peradaban manusia.Kata Kunci: Pendidikan, Moderasi, Beragama, Rahmatan lil ‘Aamin